Cartography : - Kraak, Menno Jane (Pearson Education, 2004)
This revised and updated edition integrates the latest in modern technology with traditional cartographic principles. While providing a solid conceptual foundation in cartographic methodology, the text also introduces the very latest advances that have greatly influenced cartographic techniques. The new edition reflects the increasing importance of cartography as the basis for further geographical study, the authors updating the original content and including three new chapters; Atlases, Mapping Time, and Exploratory Cartography. There will also be a more widespread emphasis on multimedia and the web, and the new edition has a companion website that will provide OHPs, show dynamics, provide an instructors manual and demonstrate more advanced cartographic techniques.